(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To study the characteristics of bacteria causing skin and soft tissue infections in diabetic patients at Nghe An Friendship General Hospital. Subjects and methods: Cross-sectional descriptive study, collecting 229 positive samples at Nghe An Friendship General Hospital from January 2023 to June 2023. Results: The most isolated infection site was foot ulcers (52.7%), followed by skin abscesses in other locations (23.6%). Cellulitis and other infections had the lowest rates. Characteristics of isolated bacterial strains: The positive culture rate reached 20.1%; In most cases, 1 agent was isolated/sample (88.2%). The Gram-positive bacteria with the highest rate was S. aureus (41.1%); The most common Gram-negative bacteria were Klebsiella pneumoniae (18.8%), followed by E. coli (9.1%). Conclusion: The most common Gram-positive bacteria were S. aureus (41.1%), the most common Gram-negative bacteria were Klebsiella pneumoniae (18.8%), followed by E. coli (9.1%). In most cases, 1 agent was isolated per sample (88.2%).